Systems Thinking Approach to Implementing Kanban: A case study. Issue 4 (5th October 2020) - Senapathi, Mali; Drury‐Grogan, Meghann L.
Abstract: Against the backdrop of the growing adoption of Kanban in a variety of software development domains, this paper reports on how a Systems Thinking approach was used to implement Kanban within a business unit of a government organization. Based on an in‐depth case study in the development organization, we describe how Kanban practices such as visualization, manage flow, classes of service, and board design were implemented. Stages in the double diamond design thinking process of exploring an issue more widely (divergent thinking) and then taking focused action (convergent thinking) were incorporated to adapt Kanban practices such as board design. Positive experiences included improved visibility, improved collaboration, and improvements in lead time. Challenges included lack of team buy‐in, setting work‐in‐progress limits, and short‐term Kanban coach. We present the key lessons learned and offer practical recommendations on how teams can better produce knowledge work in today's fast‐paced dynamic business environment. Abstract : This paper reports on how a Systems Thinking approach was used to implement Kanban within a business unit of a government organization. Stages in the design thinking process of exploring an issue more widely (divergent thinking) and then taking focused action (convergent thinking) were incorporated to adapt Kanban practices (e.g., enhancement of the board design). Positive experiences included improved visibility, improved collaboration, and improvements in lead time. Challenges included lack of team buy‐in, setting work‐in‐progress limits, and short‐term Kanban coach.